'A Shrewd Choice': Isaac Foot and Cornish politics in the General Election of 1910. (1st May 2012) - Tregidga, Garry
In March 1922 Isaac Foot was elected to the House of Commons as an Independent Liberal following a sensational by-election victory over the Conservative-Liberal Coalition of David Lloyd George in the Cornish constituency of Bodmin. As Stephen Koss wrote, the by-election 'launched what was surely the last of the great Nonconformist parliamentary careers'. Although never becoming a cabinet member, Isaac Foot was to serve as Minister of Mines in the National government from 1931-32 and his political achievements were commemorated in 1937 when he became a Privy Councillor. But it was noticeable that there was also a strong Cornish dimension to the 1922 by-election. Although Westminster issues were prominent in the contest, there was local disenchantment over the perceived failure of the government to support Cornish tin mining after the war. This article is intended as a preliminary study of the sometimes conflicting roles of Foot as a national politician and Cornish champion. After some initial reflections on Foot's career in a broader context it focuses on his initial entry into Cornish politics in 1910 when he first contested the Bodmin seat. Consideration is given to the politics of identity and the way in which deference, locality and radicalism shaped both the nature of the contest and subsequent developments.